GE_GERICHTE C/5051/2005 vom 7. Mai 2013 - GE Cour de justice (2013)
DÉPENS; MANDAT; PRÊT À USAGE; RESPONSABILITÉ DES ORGANES D'UNE SOCIÉTÉ; VALIDATION DE SÉQUESTRE | aLPC.133; aLPC.176; LP.279; CO.400; CO.402; CO.305; CO.754; CO.18